Effects of the Interactions between Dust Exposure and Genetic Polymorphisms in Nalp3, Caspase-1, and IL-1β on the Risk of Silicosis: A Case-Control Study - Weng, Shaofan; Wang, Lihua; Rong, Yi; Liu, Yuewei; Wang, Xin; Guan, Hongyu; Chen, Weihong (PloS one, 2015)
To evaluate the effects of the interactions between polymorphisms in Nalp3, caspase-1, and interleukin(IL)-1β genes and occupational dust exposure on the risk of silicosis. We conducted a population-based case-control study in a large iron mine in China. Between January 2006 and December 2009, we identified 179 patients with silicosis to evaluate as cases and 201 individuals without silicosis to evaluate as controls. We estimated cumulative dust exposure (CDE) for all subjects and we genotyped polymorphisms in Nalp3, caspase-1, and IL-1β genes. We estimated odds ratios(ORs), 95% confidence intervals(95%CIs), and p-values using logistic regression models adjusted for selected confounders. After adjusting for age, smoking status, and CDE, subjects with the CT genotype of Ex4-849C>T in Nalp3 and the GA genotype of Ex2+37G>A in caspase-1 had increased risks of silicosis (adjusted ORs[95%CIs] = 2.40 [1.12-5.12] and 3.62 [1.63-8.02], respectively). Among subjects younger than 70 years old, those with the CC genotype of IVS8-7652A>C in Nalp3 had a lower risk of silicosis than those with other genotypes (adjusted OR[95%CI] = 0.24[0.06-0.88]). Among subjects aged 70 years and older, those with the CT genotype of Ex4-849C>T in Nalp3 and those with the GA genotype of Ex2+37G>A in caspase-1 had a higher risk of silicosis than those with other genotypes (adjusted ORs [95%CI] = 2.52[1.04-6.12] and 5.19[1.88-14.35], respectively). Among subjects with CDE greater than 120 mg/m3×year and among smokers, those with the GA genotype of Ex2+37G>A in caspase-1 had a higher risk of silicosis than those with other genotypes (adjusted ORs[95%CIs] = 26.37[3.35-207.39] and 3.47[1.40-8.64], respectively). Genetic polymorphisms in Nalp3 and caspase-1 may be associated with individual susceptibility to silicosis, especially when the polymorphisms interact with age, CDE, or smoking status.